Protocolo para la instalación de apantallamiento en redes de energía eléctrica. (2023)
Through this technological project of Industrial Electromechanical Maintenance, the protocol for the installation of shielding in electrical energy networks, which serves as a basis for analyzing the processes and safety in the installation of shielding to reduce electromagnetic interference and dampen surges. The protocol presented defines a series of acts and procedures for typical shielding in electrical energy networks based on the main characteristics of the terrain, intervention structure, selection of materials, tools, developed guide thesis, among others. . The protocol has a set of detailed instructions to carry out the process of protecting electrical networks. The document provides a guide that describes the steps necessary to improve the security in the installation of these networks and therefore customer satisfaction. The logical and sequential ordering of the operations carried out when the executes an installation procedure for shielding electrical networks.